Abordagem etnometodológica acerca da co-criação de valor na graduação em administração do ensino superior privado - Brambilla, Flávio Régio (Universidade do Vale do Rio dos Sinos, 2010)
The co-creation of value is an imperative practice in the atmosphere of service. In certain cases, a superior quality condition, but in other, indispensable, as it happens in the education. Understand the education as a service encounter doesn't mean reduce the importance of that activity; means increase the quality of practices through evident parameters and previous guaranteed quality. The Private Higher Education dominates the Brazilian scenario, with numbers above the 80% of the future professional forges; the majorities are business students, which appear as the bigest category of graduated students per year. Differentiate the education saled of an education matched inside the service logic is pertinent, because in the understanding of this study, the traditional educational parameters are loaded by the ideological inclination, that could be changed for quality metrics that extrapolate simple ideology, changing that practice for concrete parameters based in the increasing of the academic quality content. Based on Self-Determination Theory and academic motivation of undergraduate students, this research aims the identification of the focal point in private education where the students as consumers are drived to a better learning experience, a hybrid prerogative, in that the student is understood as a co-producer in educational locus. Through Ethnomethodological intervention, based in the Vignettes technic applied to private higher education students, the co-creation of value was identified as an adequate practice. The results specially identify the importance of the self-determination as a central element in co-creation, stimulated by intrinsic motivation (the wish to learn) and the thin relation with extrinsic motivation (evaluation). This study identifies that the co-creation is not always well undertood by students, and they expressed at least three types of behavior (wish to co-create, the non interactive behavior because is not a commom practice, and the preference to not work collectively). The students understanding about the concept of value is limited to utility.
Keywords: Ethnomethodology; Student as co-creator; Motivation; Self-determination theory; Service logic; Co-creation of value; Educational service; Private higher education; Etnometodologia; Estudante como co-criador; Motivação; Teoria da autodeterminação; Lógica do serviço; Co-criação de valor; Serviço educacional; Educação superior privada; ACCNPQ::Ciências Sociais Aplicadas::Economia